Community geography: Toward a disciplinary framework. (October 2021) - Shannon, Jerry; Hankins, Katherine B.; Shelton, Taylor; Bosse, Amber J.; Scott, Dorris; Block, Daniel; Fischer, Heather; Eaves, LaToya E.; Jung, Jin-Kyu; Robinson, Jonnell; Solís, Patricia; Pearsall, Hamil; et al.
Community geography is a growing subfield that provides a framework for relevant and engaged scholarship. In this paper, we define community geography as a form of research praxis, one that involves academic and public scholars with the goal of co-produced and mutually-beneficial knowledge. Community geography draws from a pragmatist model of inquiry, one that views communities as emergent through a recursive process of problem definition and social action. We situate the growth of community geography programs as rooted in two overlapping but distinct traditions: disciplinary development of participatory methodologies and institutional traditions of community engagement in American higher education. We then trace the historical development of these programs, identifying common themes and outlining several challenges that community geographers should prioritize as this subfield continues to grow.